Phase change ice and snow melting steel slag aggregate, asphalt mixture and preparation method of phase change ice and snow melting steel slag aggregate
By using dual packaging technology of eutectic phase change materials and modified steel slag in asphalt mixture, the problems of phase change materials leakage and low utilization rate of steel slag are solved, and the efficient ice melting and freezing delay effect of asphalt mixture is achieved, improving the efficiency of asphalt mixture Road safety and steel slag utilization efficiency are achieved.
Patent Information
- Application Number
- CN202411095337.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-13
AI Technical Summary
Existing phase change materials are prone to leakage in asphalt pavement, and the utilization rate of steel slag is low, resulting in poor melting effect of road ice and snow and environmental pollution.
Double encapsulation is carried out using eutectic phase change materials, modified steel slag and modified cement slurry, combining styrene acrylic emulsion and glacial acetic acid solution to form a high-density and wear-resistant protective layer, improving the adsorption performance and hydration stability of steel slag, reducing Risk of leakage.
The high-temperature stability, low-temperature crack resistance and water stability of asphalt mixture are achieved, the road surface freezing time is delayed, the adhesion of snow layer is reduced, the ice and snow are effectively ablated, and the road safety and steel slag utilization efficiency are improved.
Smart Images

Figure CN119118588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering materials, and specifically to a phase-change snow-melting steel slag aggregate, an asphalt mixture and a preparation method thereof. Background Art
[0002] In winter rainy and snowy weather, the phenomenon of snow and ice on the road poses a great challenge to traffic safety. The snow and ice on the road surface significantly reduce the adhesion coefficient of vehicle tires to the road surface, and the anti-skid performance of the road surface is weakened, which not only significantly reduces the vehicle's traffic capacity, but also makes it more likely to cause traffic accidents. In addition, due to the strong reflectivity of snow to sunlight, drivers will experience "snow blindness" such as stinging eyes and tears when driving on icy and snowy roads for a long time, which in turn induces vicious traffic accidents. Traffic accidents caused by snow and ice each year account for more than 35% of the total number of winter traffic accidents, causing huge economic losses and human misfortunes. Therefore, in order to reduce the traffic accident rate, ensure smooth roads and driving safety, improve the adaptability of asphalt pavement to the service environment, and reduce the various problems that may be caused by snow and ice on roads in winter, it is necessary to take various measures and technical means to remove ice and snow from the road surface.
[0003] Solid-liquid phase change materials achieve energy storage and heat release through solid-liquid phase changes. The change from liquid to solid is an exothermic process, and the change from solid to liquid is an endothermic process. The application of phase change materials in asphalt pavements can effectively reduce the risk of temperature diseases, adjust the temperature of the pavement, and achieve active melting of ice and snow on the pavement. At the same time, steel slag, as a collection of various impurities produced in the steelmaking process, belongs to industrial solid waste. The large-scale dumping of steel slag causes environmental pollution and waste of resources. It is particularly important to achieve high-value utilization of steel slag to expand its utilization methods.
[0004] The inventor knows a steel slag-based phase change asphalt concrete that can melt snow and remove ice and a preparation method thereof (CN113979672 A), which is composed of 60% to 75% of phase change snow and ice melting steel slag coarse aggregate, 20% to 30% of natural fine aggregate, 3% to 4% of natural mineral powder, and 3% to 4% of asphalt in a mass ratio, wherein the phase change snow and ice melting steel slag coarse aggregate is prepared by steel slag particles adsorbing composite phase change materials and then coating them with cement mortar.
[0005] However, in the process of implementing the technical solutions in the embodiments of the present application, the inventors of the present application found that the above-mentioned technology has at least the following technical problems: since the phase change material is prone to leakage during the phase change process, it needs to be effectively encapsulated. During the hydration, coagulation and hardening process of the cement mortar, the asphalt concrete made by simply encapsulating the phase change material with cement mortar, the water consumed in the reaction is prone to form capillaries in the cement mortar, resulting in a large porosity and low density of the cement mortar. In addition, the chemical stability and mechanical strength of the cement mortar will decrease during long-term road use. Therefore, the phase change material still has a great risk of leakage.
[0006] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0007] The present application provides a phase-change snow and ice melting steel slag aggregate, asphalt mixture and a preparation method thereof, aiming to solve the problem that steel slag aggregate containing phase change materials and asphalt mixture thereof are prone to leakage during use, and at the same time solve the problem of serious snow and ice on asphalt pavement in winter and low utilization rate of waste steel slag.
[0008] According to the first aspect of the present disclosure, there is provided a phase change snow and ice melting steel slag aggregate, which is made of the following raw materials in parts by weight: 90-110 parts of eutectic phase change material, 190-210 parts of steel slag, 90-110 parts of modifier, 290-310 parts of styrene-acrylic emulsion, 180-200 parts of cement, and 8-12 parts of microsilica powder.
[0009] In some embodiments of the present disclosure, the cement is P.O42.5 ordinary Portland cement.
[0010] In some embodiments of the present disclosure, the eutectic phase change material is composed of decanoic acid and methyl laurate in a mass ratio of 0.24-0.28:0.72-0.76.
[0011] In some embodiments of the present disclosure, the modifier is a glacial acetic acid solution.
[0012] According to a second aspect of the present disclosure, a method for preparing the above-mentioned phase change ice and snow melting steel slag aggregate is provided, comprising the following steps: (1) Preparation of eutectic phase change material: heat n-decanoic acid to a molten state at 55-65°C, mix with methyl laurate, stir for 15-20 minutes, and then cool to room temperature. (2) Preparation method of modified steel slag: steel slag and modifier are mixed in a mass ratio of 2:0.8-1.2 and soaked for 20-25 hours and then dried at 55-65°C; (3) Preparation method of modified cement slurry: Mix cement, microsilica powder and water in a mass ratio of 1:0.03-0.07:0.3-0.7 to obtain a slurry; (4) Vacuum adsorption of phase change material by modified steel slag: the eutectic phase change material and modified steel slag are mixed in a mass ratio of 2:0.8-1.2 and vacuumed for 25-35 minutes; (5) Styrene-acrylic emulsion primary packaging: the modified steel slag vacuum adsorption phase change material and the styrene-acrylic emulsion are mixed evenly in a mass ratio of 1:2-4, allowed to stand for 15-25 minutes, and then put into cement powder for dispersion, and allowed to solidify at room temperature to obtain the product; (6) Secondary packaging of modified cement slurry: the solidified material in step (5) is placed into the modified cement slurry prepared in step (3), stirred for 10 to 20 min, then removed from the modified cement slurry, evenly spread in a container and covered with a film, left to stand for 20 to 25 h, and then cured under standard conditions for 20 to 30 d, and finally removed and sieved to obtain the product.
[0013] According to the third aspect of the present disclosure, there is provided an asphalt mixture, which is made of the following raw materials in parts by weight: 13.7 to 51 parts of the above-mentioned phase change snow and ice melting steel slag aggregate, 18.2 to 53.2 parts of natural coarse aggregate, 26.2 to 28.1 parts of natural fine aggregate, 4.7 to 5.0 parts of mineral powder, and 5.0 to 5.6 parts of asphalt.
[0014] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The phase-change snow-melting steel slag aggregate of this application is an environmentally friendly, non-toxic, and non-corrosive material that can give asphalt mixture a temperature-regulating function and can achieve active melting of snow and ice on asphalt pavements in winter.
[0015] 2. The raw materials used in the phase change snow and ice melting steel slag aggregate of this application are non-toxic and harmless, the raw materials are widely available, the production process is pollution-free, the price is low, the preparation process is simple, and it has good economic benefits.
[0016] 3. The phase change material contained in the phase change snow and ice melting steel slag aggregate of the present application is compounded with decanoic acid and methyl laurate. The developed eutectic phase change material has a suitable phase change temperature and a large phase change enthalpy value. Its heat absorption range is concentrated in 1.8~9.41℃, the phase change latent heat is 182.2J / g, and the heat release range is concentrated in -4.99~1.35℃, which can meet the needs of road surface temperature control and snow melting in winter.
[0017] 4. The present application modifies the surface of steel slag by using glacial acetic acid solution to dissolve some mineral components in the steel slag, such as calcium carbonate (CaCO3), calcium hydroxide (Ca(OH)2) and dicalcium ferrite (CaO·Fe2O3), to generate calcium acetate (Ca(OAc)2), accompanied by the generation of pores. The improvement of these pore structures helps to increase the specific surface area of the steel slag and increase its contact area with the external environment, thereby improving its adsorption performance. At the same time, the glacial acetic acid solution activates the hydration performance of the steel slag to a certain extent, so that the modified steel slag generates hydration products such as silica gel and calcium silicate hydrate (CSH) gel during the hydration process. These hydration products help to improve the volume stability of the steel slag.
[0018] 5. The preparation and packaging process of the phase change snow and ice melting steel slag aggregate in the present application adopts a two-step packaging process, firstly, the steel slag adsorbed with eutectic phase change material is packaged once with styrene acrylic emulsion to form a dense flexible structural layer, and then it is packaged for a second time with modified cement slurry, wherein the modified cement slurry activates a large amount of active SiO2 contained therein, and reacts with the hydration product Ca(OH)2 during the cement hydration process to generate a dense CSH gel, which fills the capillaries and increases the strength and density of the cement. Therefore, a high-strength, wear-resistant protective layer can be formed on the basis of the first packaging, thereby effectively solving the problem that the steel slag aggregate containing phase change materials and its asphalt mixture are prone to leakage during use.
[0019] 6. The asphalt mixture containing phase-changing ice-melting steel slag aggregate in the present application not only has stronger high-temperature stability, low-temperature crack resistance and water stability than ordinary asphalt, but also has excellent ice-melting ability, which can delay the freezing time of the road surface, reduce the adhesion between the road surface and the snow layer, and realize the active melting of ice and snow on the road surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 These are the results of a snow melting test in one embodiment of the present application; wherein, a: snow accumulation on the specimen surface after 1 hour; b: snow accumulation on the specimen surface after 2 hours; c: snow accumulation on the specimen surface after 3 hours. DETAILED DESCRIPTION
[0021] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0022] Unless otherwise specified, the pesticide and adjuvant raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, application methods and test methods involved are all conventional methods unless otherwise specified.
[0023] In the following examples, the phase-change snow-melting steel slag aggregate is added to the asphalt mixture in an equal volume replacement manner, and the asphalt mixture includes the following preparation steps: Phase change melting ice and snow steel slag aggregate: 100 parts of eutectic phase change material, 190-210 parts of steel slag, 90-110 parts of modifier (glacial acetic acid solution with a volume concentration of 15%), 290-310 parts of styrene-acrylic emulsion, 180-200 parts of cement (P.O42.5 ordinary Portland cement), and 8-12 parts of microsilica powder.
[0024] Phase change snow and ice melting steel slag asphalt mixture: phase change snow and ice melting steel slag aggregate 13.7 to 51 parts, natural coarse aggregate 18.2 to 53.2 parts, natural fine aggregate 26.2 to 28.1 parts, mineral powder 4.7 to 5.0 parts, asphalt 5.0 to 5.6 parts.
[0025] (1) Preparation of eutectic phase change material: prepare the raw materials according to the above weight ratio; heat n-decanoic acid to a molten state at 60°C, weigh n-decanoic acid and methyl laurate (mass ratio of 0.26:0.74), and then stir with a glass rod for 5 minutes, and then stir with a magnetic stirrer for 10 minutes, and cool to room temperature.
[0026] (2) Preparation of modified steel slag: Mix steel slag and 15% glacial acetic acid solution in a mass ratio of 2:1 and soak for 24 hours, then dry at 60°C.
[0027] (3) Preparation method of modified cement slurry: Mix cement (P.O42.5 ordinary Portland cement), microsilica powder and water in a mass ratio of 1:0.05:0.5.
[0028] (4) Modified steel slag vacuum adsorption phase change material: Mix the modified steel slag and the eutectic phase change material in a mass ratio of 2:1 and put them into a vacuum pump. Close the vacuum valve and vacuum for 30 minutes.
[0029] (5) One-time packaging of styrene-acrylic emulsion: Mix the modified steel slag vacuum adsorption phase change material and styrene-acrylic emulsion in a mass ratio of 1:3, wait for 20 minutes, and take out the steel slag after ensuring that the surface of the steel slag is completely coated with styrene-acrylic emulsion. After taking out, put it into cement powder for dispersion, and wait for it to solidify at room temperature.
[0030] (6) Secondary packaging of modified cement slurry: Place the solidified material in step (5) into the prepared modified cement slurry and stir for 15 min. Then remove it from the cement slurry and spread it evenly on a porcelain plate with plastic paper. Then cover it with a layer of plastic wrap to prevent the surface cement stone from cracking due to rapid evaporation of water. After standing for 24 h, cure it under standard conditions (temperature 18-22°C, relative humidity ≥90%) for 28 days. After 28 days, take it out and classify it using a shaking screen.
[0031] (7) The phase change melting ice and snow steel slag aggregate, natural coarse aggregate, fine aggregate, mineral powder and SBS modified asphalt are fully mixed and mechanically stirred at 180°C for 3 minutes.
[0032] Example 1. A phase-change snow-melting steel slag asphalt mixture is made from the following raw materials in parts by weight: 13.7 parts of phase change snow-melting steel slag aggregate, 53.2 parts of natural coarse aggregate, 28.1 parts of natural fine aggregate, 5 parts of limestone powder, and 5 parts of SBS modified asphalt; among them, the phase change snow-melting steel slag aggregate is 5-10mm and 10-15mm, the natural coarse aggregate is 3-5mm basalt, and the fine aggregate is 0-3mm limestone chips.
[0033] Example 2. A phase-change snow-melting steel slag asphalt mixture is made from the following raw materials in parts by weight: 26.7 parts of phase change snow-melting steel slag aggregate, 41 parts of natural coarse aggregate, 27.4 parts of natural fine aggregate, 4.9 parts of limestone powder, and 5.3 parts of SBS modified asphalt; among them, the phase change snow-melting steel slag aggregate is 5-10mm and 10-5mm, the natural coarse aggregate is 3-5mm basalt, and the fine aggregate is 0-3mm limestone chips.
[0034] Example 3. A phase-change snow-melting steel slag asphalt mixture is made from the following raw materials in parts by weight: Phase change snow-melting steel slag aggregate 39.1 parts, natural coarse aggregate 29.4 parts, natural fine aggregate 26.8 parts, limestone slag powder 4.8 parts, SBS modified asphalt 5.4 parts; among them, the phase change snow-melting steel slag aggregate is 5-10mm and 10-15mm, the natural coarse aggregate is 3-5mm basalt, and the fine aggregate is 0-3mm limestone chips.
[0035] Example 4. A phase-change snow-melting steel slag asphalt mixture is made from the following raw materials in parts by weight: 51 parts of phase change snow-melting steel slag aggregate, 18.2 parts of natural coarse aggregate, 26.2 parts of natural fine aggregate, 4.7 parts of limestone powder, and 5.6 parts of SBS modified asphalt; among them, the phase change snow-melting steel slag aggregate is 5-10mm and 10-15mm, the natural coarse aggregate is 3-5mm basalt, and the fine aggregate is 0-3mm limestone chips.
[0036] In addition, five different types of asphalt mixtures were prepared according to the above preparation method, namely, an asphalt mixture without phase change material, a phase change steel slag asphalt mixture encapsulated only once with styrene acrylic emulsion, a phase change steel slag asphalt mixture encapsulated only once with modified cement slurry, a phase change steel slag asphalt mixture encapsulated twice with ordinary cement slurry and styrene acrylic emulsion, and a phase change steel slag asphalt mixture encapsulated once with ordinary cement as a comparison example.
[0037] Comparative Example 5. A common AC-13C asphalt mixture is made from the following raw materials in parts by weight: 24 parts of 10-15mm natural coarse aggregate, 22 parts of 5-10mm natural coarse aggregate, 16 parts of 3-5mm natural coarse aggregate, 34 parts of 0-3mm natural fine aggregate, 4 parts of mineral powder, and 4.9 parts of SBS modified asphalt; among them, the natural coarse aggregate is basalt and the natural fine aggregate is limestone chips.
[0038] Comparative Example 6. A phase-change steel slag asphalt mixture encapsulated once by styrene acrylic emulsion is made of the following raw materials in parts by weight: 49.4 parts of phase-change ice-melting steel slag aggregate, 18.8 parts of natural coarse aggregate, 27 parts of natural fine aggregate, 4.8 parts of limestone mineral powder, and 4.8 parts of SBS modified asphalt; wherein the phase-change ice-melting steel slag aggregate is 5-10 mm and 10-15 mm, the natural coarse aggregate is 3-5 mm basalt, and the fine aggregate is 0-3 mm limestone chips.
[0039] Comparative Example 7. A phase change steel slag asphalt mixture encapsulated once by modified cement slurry is made of the following raw materials in parts by weight: 50.2 parts of phase change ice and snow melting steel slag aggregate, 18.5 parts of natural coarse aggregate, 26.6 parts of natural fine aggregate, 4.8 parts of limestone mineral powder, and 5.6 parts of SBS modified asphalt; wherein the phase change ice and snow melting steel slag aggregate is 5-10 mm and 10-15 mm, the natural coarse aggregate is 3-5 mm basalt, and the fine aggregate is 0-3 mm limestone chips.
[0040] Comparative Example 8. A phase-change steel slag asphalt mixture that is secondary encapsulated using ordinary cement slurry and styrene-acrylic emulsion is made of the following raw materials in parts by weight: 50.2 parts of phase-change ice-melting steel slag aggregate, 18.5 parts of natural coarse aggregate, 26.6 parts of natural fine aggregate, 4.7 parts of limestone mineral powder, and 5.8 parts of SBS modified asphalt; wherein the phase-change ice-melting steel slag aggregate is 5-10 mm and 10-15 mm, the natural coarse aggregate is 3-5 mm basalt, and the fine aggregate is 0-3 mm limestone chips.
[0041] Comparative Example 9. A phase-change steel slag asphalt mixture encapsulated once with ordinary cement is made of the following raw materials in parts by weight: 50.2 parts of phase-change ice-melting steel slag aggregate, 18.5 parts of natural coarse aggregate, 26.6 parts of natural fine aggregate, 4.8 parts of limestone mineral powder, and 6 parts of SBS modified asphalt; wherein the phase-change ice-melting steel slag aggregate is 5-10 mm and 10-15 mm, the natural coarse aggregate is 3-5 mm basalt, and the fine aggregate is 0-3 mm limestone chips.
[0042] The phase-change steel slag asphalt mixture in the above embodiment was subjected to road performance test, temperature adjustment test, ice melting test and snow melting test. The road performance test items include rutting test, low temperature bending test, immersion Marshall test, freeze-thaw splitting test, and volume stability test. The road performance tests were all carried out in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTGE20-2011). The temperature adjustment test used a low-temperature environmental box to simulate the cooling process, with a temperature change range of 20°C to -10°C and a time range of 0s to 6300s. A K-type thermocouple wire was used as a sensing device, and a temperature recorder was used to record the internal temperature of the specimen at intervals of 10s. The ice melting test was carried out in accordance with the ice melting rate test in the "Ice and Snow Melting Materials for Highway Asphalt Mixtures" (JT / T1210. 1-2018). The snow melting test was carried out using an outdoor actual snowfall test. The above test was used to test the performance of the phase change snow and ice melting steel slag asphalt mixture of the present application, and compared with the ordinary asphalt mixture. The test results are shown in Tables 1 to 3 and Figure 1 .
[0043] Table 1 Road performance test of phase change steel slag asphalt mixture .
[0044] Table 2 Temperature adjustment test of phase change steel slag asphalt mixture .
[0045] Table 3 Phase change steel slag asphalt mixture ice melting test .
[0046] As can be seen from Table 1, the phase-change snow-melting steel slag aggregate provided by the present application meets the relevant technical requirements of the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004) standard, and its dynamic stability, maximum bending-tensile strain, residual stability, splitting strength ratio and volume expansion rate are better than those of ordinary asphalt mixtures. And compared with the phase-change steel slag aggregate encapsulated once with styrene-acrylic emulsion, the phase-change snow-melting steel slag aggregate provided by the present application has better high-temperature rutting resistance; compared with the phase-change steel slag aggregate encapsulated only once with modified cement slurry, twice with ordinary cement slurry and styrene-acrylic emulsion, and once with ordinary cement, the phase-change snow-melting steel slag aggregate provided by the present application has better resistance to water damage and expansion inhibition. From Tables 2, 3 and Figure 1 It can be seen that the phase-changing ice and snow melting steel slag aggregate provided in the present application can make the asphalt mixture have excellent temperature regulating function, can give the asphalt mixture excellent ice-melting ability, can delay the freezing time of the road surface, reduce the adhesion between the road surface and the snow layer, and realize the active melting of ice and snow on the road surface.
[0047] The present application has been described in detail above in conjunction with the embodiments. However, those skilled in the art will appreciate that, without departing from the spirit and scope of the present application, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. A phase change snow and ice melting steel slag aggregate, characterized in that: It is composed of the following raw materials in parts by weight: 90-110 parts of eutectic phase change material, 190-210 parts of steel slag, 90-110 parts of modifier, 290-310 parts of styrene-acrylic emulsion, 180-200 parts of cement, and 8-12 parts of microsilica powder.
2. The phase change ice and snow melting steel slag aggregate according to claim 1 is characterized in that: The cement is P.O42.5 ordinary Portland cement.
3. The phase change snow and ice melting steel slag aggregate according to claim 1 is characterized in that: The eutectic phase change material is composed of n-decanoic acid and methyl laurate in a mass ratio of 0.24-0.28:0.72-0.
76.
4. The phase change ice and snow melting steel slag aggregate according to claim 1, characterized in that: The modifier is glacial acetic acid solution.
5. The method for preparing the phase-change snow-melting steel slag aggregate according to claim 1, characterized in that: The following steps are involved: (1) Preparation of eutectic phase change material: heat n-decanoic acid to a molten state at 55-65°C, mix with methyl laurate, stir for 15-20 minutes, and then cool to room temperature. (2) Preparation method of modified steel slag: steel slag and modifier are mixed in a mass ratio of 2:0.8-1.2 and soaked for 20-25 hours and then dried at 55-65°C to obtain the modified steel slag; (3) Preparation method of modified cement slurry: Mix cement, microsilica powder and water in a mass ratio of 1:0.03-0.07:0.3-0.7 to obtain a slurry; (4) Vacuum adsorption of phase change material by modified steel slag: the eutectic phase change material and modified steel slag are mixed in a mass ratio of 2:0.8-1.2 and vacuumed for 25-35 minutes; (5) Styrene-acrylic emulsion primary packaging: the modified steel slag vacuum adsorption phase change material and the styrene-acrylic emulsion are mixed evenly in a mass ratio of 1:2-4, allowed to stand for 15-25 minutes, and then put into cement powder for dispersion, and allowed to solidify at room temperature to obtain the product; (6) Secondary packaging of modified cement slurry: the solidified material in step (5) is placed into the modified cement slurry prepared in step (3), stirred for 10 to 20 min, then removed from the modified cement slurry, evenly spread in a container and covered with a film, left to stand for 20 to 25 h, and then cured under standard conditions for 20 to 30 d, and finally removed and sieved to obtain the product.
6. An asphalt mixture, characterized in that: The material is made of the following raw materials in parts by weight: 13.7 to 51 parts of the phase change snow-melting steel slag aggregate as described in claim 1, 18.2 to 53.2 parts of natural coarse aggregate, 26.2 to 28.1 parts of natural fine aggregate, 4.7 to 5.0 parts of mineral powder, and 5.0 to 5.6 parts of asphalt.
